Analysis of News Framing of Political Elites on Tempo.com and Detik.com (Case Study: The Meeting Between Prabowo and Megawati on April 7, 2025) - Alia Salamah (Publikasi Indonesia, 2026)
The media has a strategic role in shaping public perception of the dynamics of the political elite. The meeting between Prabowo Subianto and Megawati Soekarnoputri after the 2024 election is an important event that is full of symbolic and strategic meaning, but the limitation of information opens up space for the media to construct reality through framing. This research aims to analyze how Tempo.co and Detik.com frame the event and identify the differences in the resulting political reality constructions. The research used a qualitative approach with a constructivist paradigm and Robert Entman's model framing analysis method combined with Pan and Kosicki. The analysis unit consists of 5 news from Tempo.co and 5 news from Detik.com news in the period 7–14 April 2025. The results of the study show that Tempo.co frame the meeting as a strategic political event related to the consolidation of power, coalition dynamics, and the potential for cabinet reshuffle. Instead, Detik.com frame the event as a political gathering by highlighting aspects of national harmony, stability, and reconciliation. The difference in framing can be seen in the choice of issues, narrative structure, and use of language. This study concludes that the media is not neutral, but actively constructs political reality. These findings strengthen the framing theory and construction of social reality and affirm the importance of media literacy in understanding the bias of political reporting.